Ancient harp seal hunters of Disko Bay (Vol. 330):Subsistence and settlement at the Saqqaq culture site Qeqertasussuk (2400-1400 BC), West Greenland - Morten Meldgaard (Monographs on Greenland | Meddelelser om Grønland, 2004)
The Saqqaq Culture site Qeqertasussuk (2400-1400 BC) is situated in the south easterncorner of Disko Bay, West Greenland. The site was excavated between 1983 and 1987 byQasigiannguit Museum. The stratified cultural deposits are exceptionally well preservedby permafrost and yielded hundreds of thousands of animal bones, feathers, plantremains, insect remains, wooden implements, and a wealth of other organic refuse aswell as stone tools, house ruins, stone set fireplaces and other traces of habitation. In order to understand the life conditions of the inhabitants at Qeqertasussuk, acomparative survey of the historic distribution, density and availability of the livingresources in the area is undertaken. This resource model is then evaluated against thepaleo-environmental data. Also, comparative ethnohistorical and ethnographic data onthe exploitation of the living resources in the area is presented. Subsistence and subsistence change at Qeqertasussuk is studied through a comprehensiveanalysis of the faunal material that consists of more than 200,000 animal bones.Quantitative methods are supplemented by detailed studies of seasonality and age compositionof the hunting bag. Forty three species of animals are represented. Harp sealand ringed seal represent the most important game, but sea birds such as fulmar,Brünnich's guillemot, and little auk also play a significant role in the subsistence economy.Fish, especially Atlantic Cod, have been caught and remains of large whales indicatethat these animals were utilized, but it can not be decided whether they were activelyhunted. Most of the game was taken close by the site, however finds of caribou indicatethat inland caribou hunting was undertaken and that Qeqertasussuk was part of a largersubsistence-settlement-system. Several species of plants were also utilized. Temporal changes in the composition of the faunal material indicate that significantchanges occur in the subsistence at Qeqertasusuk. Four phases are identified: (1) Basecampperiod I (2400-2100 BC). A pioneer phase where the site is used as a year-roundbase camp with more than 90% of the biomass being harvested within an area ofapproximately 80 km2, (2) Base-camp period II (2100-1900 BC), which seems to be theperiod of most intensive use and where new methods (probably netting) of harp sealhunting are introduced, (3) Hunting camp period (1900-1700 BC), where the sitebecomes more specialized and more seasonal with a focus on spring-summer huntingfor harp seals, (4) high activity period (1700-1400 BC) indications of continued heavysea mammal hunting. The site was abandoned around 1400 BC. The causes of the abandonment of Qeqertasussukis discussed and the impact of the general cooling around 1500 BC on keyresources such as harp seal and capelin is highlighted.